First results of oceanographic works on Ukrainian longline vessels in Antarctica (CCAMLR zone) in 2017 / 2018 season - Paramonov, V.V. (Український антарктичний журнал, 2019)
Aim of works is implementation of duties, taken by Ukraine on XXXVI Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) Session and study of habitation of main fishing objects in Antarctica waters. Methods of works were the use of DST CTD recorder produced by STAR OGGICompany (Iceland) and the analysis of the obtained data. Results of works include 36 longline and 11 other stations (on a line, on streamer, on Juday plankton net) executed in Amundsen, Ross and Weddell Seas during the period from December 2017 to April 2018. Vertical changeability of temperature, temporal changeability of benthic temperature were analyzed; spatial changeability of temperatures in separate Seas was found out; 4 basic water masses were distinguished, influence of bottom temperature to the catches of Antarctic toothfish was analyzed. Conclusion was made about the increase in catches while lowering the bottom temperature in Weddell Sea. З метою виконання обов’язків, взятих Україною на XXXVI сесії Комісії зі збереження морських живих ресурсів Антарктики (ККАМЛР) та вивчення умов проживання основних об’єктів промислу у водах Антарктики на українських риболовних судах, які вели промисел іклача, українські спостерігачі, окрім своїх основних завдань, здійснювали також деякі океанологічні роботи. Методами робіт було використання самопису DST CTD ісландської фірми STAR OGGI та аналіз отриманих даних. Результати робіт включають в себе 36 приярусних та 11 інших станцій (на фалі, на стрімері, на сітці Джеді), які були виконані в морях Амундсена, Роса та Ведделла у період з грудня 2017 по квітень 2018 року трьома українськими судами («Сімеїз», «Кореїз» та «Каліпсо»). На основі отриманих матеріалів була проаналізована вертикальна мінливість температури, яка звичайно знижувалась від поверхні до глибин 70—250 м, потім зростала до глибин 300—400 м і далі знижувалась.